One- Versus Two-Stent Stenting Strategies in Coronary Bifurcation Lesions - Chan Z.; Alexandrou M.; Strepkos D.; Mutlu D.; Carvalho P. E. P.; Krestyaninov O.; Khelimskii D.; Kultursa B.; Karagoz A.; Yıldırım U.; et al. (My University, 2026)
Objectives. Additional studies are needed on the follow-up outcomes of 1-vs 2-stent techniques in bifurcation percutaneous coronary interventions (PCI). Methods. The authors examined the angiographic and procedural characteristics, and outcomes of 1306 bifurcation PCIs (1139 patients) performed at 6 centers between 2014 and 2024 from the PROGRESS-BIFURCATION registry. Results. Upfront 1-stent PCI (96.2% provisional stenting, 2% mini crush with 1 stent, 1.7% side branch [SB] stent only) was used in 75.5% of lesions; upfront 2-stent PCI was used in 24.5% (48.1% double kissing crush, 16.9% culotte, 35% other). Patients treated with an upfront 2-stent strategy were older (68 +/- 12 vs 66 +/- 12 years; P = .011) and more likely to have dyslipidemia (82.7% vs 76.0%; P = .019) and a history of heart failure (27.6% vs 20.3%; P = .011). An upfront 2-stent strategy was more common in left main bifurcations and lesions with moderate/severe calcification or larger SB diameter. Upfront 2-stent strategies required longer procedure and fluoroscopy times and higher patient radiation dose but similar contrast volume. Two-stent strategies were associated with higher technical success (98.4% vs 94.4%; P = .003), but similar procedural success (93.5% vs 90.4%; P = .116) and in-hospital major adverse cardiac events (MACE) (5.2% vs 3.9%; P = .355) compared with 1-stent strategies. Follow-up data was available for 783 patients. During a median follow-up of 1095 days, patients treated with an upfront 2-stent strategy had similar incidence of MACE, target vessel revascularization, myocardial infarction, and all-cause mortality (adjusted hazard ratio for mortality, 0.99; 95% CI, 0.61-1.62; P = .98). Conclusions. Upfront 1-vs 2-stent bifurcation PCI was associated with similar procedural success and follow-up outcomes during a median follow-up of 3 years.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Kalp ve Kalp Damar Sistemleri; Klinik Tıp; Klinik Tıp (Med); Cardiac & Cardiovascular Systems; Clinical Medicine; Clinical Medicine (Med); Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine